Therapeutic Potential of Targeting Periostin in the Treatment of Graves’ Orbitopathy - Jang, Sun Young; Kim, Jinjoo; Park, Jung Tak; Liu, Catherine Y.; Korn, Bobby S.; Kikkawa, Don O.; Lee, Eun Jig; Yoon, Jin Sook (Frontiers in Endocrinology, 2022)
Periostin is a matricellular protein that is ubiquitously expressed in normal human tissues and is involved in pathologic mechanism of chronic inflammatory and fibrotic disease. In this study we investigate periostin in the pathogenesis of Graves’ orbitopathy (GO) using human orbital adipose tissue obtained from surgery and primary cultured orbital fibroblasts in vitro. POSTN (gene encoding periostin) expression in Graves’ orbital tissues and healthy control tissues was studied, and the role of periostin in GO pathologic mechanism was examined through small-interfering RNA (siRNA)-mediated silencing. POSTN gene expression was significantly higher in Graves’ orbital tissues than healthy control tissues in real-time PCR results, and immunohistochemical staining revealed higher expression of periostin in Graves’ orbital tissues than normal tissues. Silencing periostin using siRNA transfection significantly attenuated TGF-β-induced profibrotic protein production and phosphorylated p38 and SMAD protein production. Knockdown of periostin inhibited interleukin-1 β -induced proinflammatory cytokines production as well as phosphorylation of NF-κB and Ak signaling protein. Adipocyte differentiation was also suppressed in periostin-targeting siRNA transfected GO cells. We hypothesize that periostin contributes to the pathogenic process of inflammation, fibrosis and adipogenesis of GO. Our study provides in vitro evidence that periostin may be a novel potential therapeutic target for the treatment of GO.